Mapping the Canadian library and information science research landscape - Munroe-Lynds, Cora-Lynn; Simard, Marc-André; Li, Vinson; McClean, Emily; Mongeon, Philippe (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2021)
<span data-sheets-value=""1":2,"2":"This work-in-progress paper aims to map the scholarship produced by the eight Canadian Library and Information Science (LIS) schools. After using the citation network to divide publications into several research areas, we analyze how the research output of different LIS schools is distributed across these areas, in an attempt to shed light on the schools’ specificities and commonalities and how each school contributes to the global picture of Canadian LIS research."" data-sheets-userformat=""2":8961,"3":"1":0,"11":0,"12":0,"16":12">This work-in-progress paper aims to map the scholarship produced by the eight Canadian Library and Information Science (LIS) schools. After using the citation network to divide publications into several research areas, we analyze how the research output of different LIS schools is distributed across these areas, in an attempt to shed light on the schools’ specificities and commonalities and how each school contributes to the global picture of Canadian LIS research.